Case Report: Endocrine, immune and disease dynamics in a patient with rheumatoid arthritis during flare and medication change - Seizer, Lennart; Gostner, Johanna M.; Garbers, Christoph; Licht, Melina; Sager, Sebastian; Brandl, Andreas; Schubert, Christian (Frontiers in Immunology, 2025)
ObjectiveRheumatoid arthritis (RA) is a chronic autoimmune disease of mostly unknown etiology and pathophysiology. In this integrative single-case study on a patient with RA, we had the unique opportunity to closely monitor the individual dynamics of endocrine, immune and disease variables during a naturally occurring flare-up and subsequent medication change.MethodsThe 59-year-old female RA patient collected her entire urine over 30 days in 12-h intervals (60 consecutive measurements in total). Subsequently, cortisol, interleukin-6 (IL-6), orosomucoid-2 (ORM-2), neopterin and creatinine levels were determined in the urine samples. Further, each morning and evening, the patient completed the DIARI, a set of questionnaires on variables such as perceived pain, perceived RA disease activity and emotional states. Once a week, the patient was interviewed online and had an appointment with her rheumatologist, in which several indices of RA disease activity were determined: SDAI, CDAI and DAS28. From these data various time series were constructed for statistical analysis.ResultsRA disease state increased from low to high activity during the first 12 study days. Thereupon, the medication was changed, which proved effective in reducing RA disease activity. However, the levels of urinary neopterin, urinary IL-6 and urinary ORM-2 did not show any response, neither to the increasing disease activity nor the medication change. The patient’s daily reports on pain, RA disease activity, emotional states and body temperature, however, mirrored the course of the rheumatologic indices.ConclusionThis integrative single-case study clearly demonstrated the importance of process analysis for the evaluation of therapeutic measures in RA. In the studied patient, urinary levels of neopterin, IL-6 and ORM-2 were not found to be appropriate biomarkers of short-term fluctuations in RA disease activity. Instead, the results reported by the patient proved to be a useful tool for ambulatory and longitudinal monitoring of RA.